Connecting University Students, Faculty and Administrators through an Online SMS Service - Reima Al-Jarf (Borong Newinera Publisher, 2021)
King Saud University (KSU) created an online Short Message Service (SMS) called “Tawasul”, developed in house, to connect administrators, faculty, and students. The KSU rector, deans, department heads and program coordinators send group season’s greetings and notifications to the mobile phones of faculty members, staff, and students. Instructors can send course notifications to their students regarding exams and other issues. There are currently 380 SMS groups for department staff, T.A.’s, workshop participants, course enrollees and others. Students and faculty surveyed indicated that the KSU online SMS Service is easy to use. It is faster and more efficient than paper memos and e-mails, especially in emergency situations. It helps conserve paper. Students and faculty can be reached anytime, anywhere and 7 days a week. Unused SMS in the user’s account can be added to his/her balance. SMSs are archived. Those interested to join a group can send a message to the group’s mobile number. Students’ mobile phone numbers are entered manually once and saved as a group. However, some faculty indicated that the allocated 200 free SMSs per month are not enough when class enrollees are more than 50. They also indicated that it is not possible to send a reply, a comment, or a query to the sender of the SMS. Sometimes the service cannot be used when it is under maintenance or when there is a technical problem. It is time-consuming to enter students’ mobile phone numbers manually particularly in large classes. Further results and recommendations are given.